Satisfaction and continuation with LNG-IUS 12: findings from the real-world kyleena® satisfaction study. (2nd November 2021) - Stovall, Dale W.; Aqua, Keith; Römer, Thomas; Donders, Gilbert; Sørdal, Terje; Hauck, Brian; Llata, Eric Saucedo de la; Kallner, Helena Kopp; Salomon, Julie; Zvolanek, Michal; Frenz, Ann-Kathrin; Böhnke, Tanja; et al.
Abstract: Purpose: The Kyleena ® Satisfaction Study (KYSS) aimed to assess satisfaction and continuation with levonorgestrel-releasing intrauterine system (LNG-IUS) 12 (Kyleena ® ) in routine clinical practice and to evaluate factors that influence satisfaction. Materials and methods: This prospective, observational, multicentre, single-arm cohort study, with 1-year follow-up, was conducted in Belgium, Canada, Germany, Mexico, Norway, Sweden, Spain and the United States from 2017 to 2018. During routine counselling, women who independently selected to use LNG-IUS 12 were invited to participate in the study. KYSS assessed LNG-IUS 12 satisfaction, continuation and safety. Results: Overall, there were 1126 successful LNG-IUS 12 placements, with insertion attempted in 1129 women. Most participants (833/968, 86.1%, 95% CI 83.7–88.2%, with satisfaction outcome data available) reported satisfaction with LNG-IUS 12 at 12 months (or at the final visit if the device was discontinued prematurely). Satisfaction was not associated with age, parity or motivation for choosing LNG-IUS 12. The majority of women (919/1129, 81.4%) chose to continue after 12 months. Discontinuation was not correlated with age or parity. Overall, 191 women (16.9%) reported a treatment-emergent adverse event. Conclusions: Results from KYSS provide the first real-world evidence assessing LNG-IUS 12, and demonstrate high satisfaction and continuation rates irrespective of age or parity. Clinical trial registration: NCT03182140